WW domain-mediated interactions reveal a spliceosome-associated protein that binds a third class of proline-rich motif: The proline glycine and methionine-rich motif - Bedford, Mark T. (The National Academy of Sciences, 1998)
Pre-mRNA splicing requires the bridging of the 5′ and 3′ ends of the intron. In yeast, this bridging involves interactions between the WW domains in the splicing factor PRP40 and a proline-rich domain in the branchpoint binding protein, BBP. Using a proline-rich domain derived from formin (a product of the murine limb deformity locus), we have identified a family of murine formin binding proteins (FBP’s), each of which contains one or more of a special class of tyrosine-rich WW domains. Two of these WW domains, in the proteins FBP11 and FBP21, are strikingly similar to those found in the yeast splicing factor PRP40. We show that FBP21 is present in highly purified spliceosomal complex A, is associated with U2 snRNPs, and colocalizes with splicing factors in nuclear speckle domains. Moreover, FBP21 interacts directly with the U1 snRNP protein U1C, the core snRNP proteins SmB and SmB′, and the branchpoint binding protein SF1/mBBP. Thus, FBP21 may play a role in cross-intron bridging of U1 and U2 snRNPs in the mammalian A complex.